2005
DOI: 10.1529/biophysj.104.048959
|View full text |Cite
|
Sign up to set email alerts
|

Shape Transitions and Lattice Structuring of Ceramide-Enriched Domains Generated by Sphingomyelinase in Lipid Monolayers

Abstract: Sphingomyelinases (SMases) hydrolyze the membrane constituent sphingomyelin (SM) to phosphocholine and ceramide (Cer). Growing evidence supports that SMase-induced SM-->Cer conversion leads to the formation of lateral Cer-enriched domains which drive structural reorganization in lipid membranes. We previously provided visual evidence in real-time for the formation of Cer-enriched domains in SM monolayers through the action of the neutral Bacillus cereus SMase. In this work, we disclose a succession of discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 74 publications
5
83
0
Order By: Relevance
“…As a consequence, equilibration of enzyme between vesicles is slow compared to establishment of steady state kinetics (Yu et al, 2005a(Yu et al, , 2002. Similarly, studies of SMase activity for monolayers at the air-water interface have concluded that all interfacial-activated enzyme is associated irreversibly with the interface (Fanani et al, 2002;Hartel et al, 2005).…”
Section: Kinetics Of Membrane Restructuringmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, equilibration of enzyme between vesicles is slow compared to establishment of steady state kinetics (Yu et al, 2005a(Yu et al, , 2002. Similarly, studies of SMase activity for monolayers at the air-water interface have concluded that all interfacial-activated enzyme is associated irreversibly with the interface (Fanani et al, 2002;Hartel et al, 2005).…”
Section: Kinetics Of Membrane Restructuringmentioning
confidence: 99%
“…Thus, the increase in dye-excluded area cannot be directly related to the extent of SM hydrolysis. The situation is different for SM monolayers where changes in surface area due to enzymatic production of the smaller ceramide molecule are proportional to the extent of SM hydrolysis (Fanani et al, 2002;Hartel et al, 2005). Previous studies of PLA 2 have employed conditions where initial bilayer changes were attributable to single enzymes (Balashev et al, 2007).…”
Section: Kinetics Of Membrane Restructuringmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been indicated that lateral enzyme-specific out-of equilibrium organization of lipid domains represents a new level of signal transduction from local (nm) to long-range (μm) scales (Hartel et al, 2005). Cross-talk between lateral domain structures and dipolar electrostatic fields certainly adds new dimensions to the mechanisms of SMase-mediated signal transduction in biological membranes.…”
Section: Ceramide-dependent Raft Systemmentioning
confidence: 99%
“…As a consequence, such Cers form segregated solid-like condensed domains, in both bilayers and monolayers, that even exclude fluorescent probes and proteins (Carrer and Maggio 1999;Holopainen et al 2001;Härtel et al 2005;Castro et al 2007;Chiantia et al 2008;Busto et al 2009;Karttunen et al 2009;López-Montero et al 2010). Natural mixtures of Cer are mainly composed of long chain Cers.…”
Section: Ceramide Mixturesmentioning
confidence: 99%